Pakistan-Bangladesh Relations During Hasina Wajid Era: An Analysis - Bashir Hussain Shah,; Muhammad Ahsan,; Dr. Ghulam Mustafa ,; Ziarat Ali, (Dialogue Social Science Review (DSSR), 2025)
The Main purpose of this study is to examine the relationship Between Pakistan and Bangladesh during Hasina Wajid Era. The relations were marked as sour because of Awami league inclined towards India. This study uses a qualitative research approach to elucidate the relations between the two. The results of this study underline the intricacy of Pak-Bangladesh ties and draw attention to the possibilities as well as the difficulties. The study ends with suggestions for both sides of legislators on ways to improve cooperation and settle long-standing problems. This study adds to the scholarly debate on South Asian foreign affairs and offers insightful analysis for academics, diplomats, and legislators eager in promoting regional stability and cooperation.